The problem of psychological reality of conceptual metaphors - Kiklewicz, Aleksander (Papers in Linguistics, 2021)
The article discusses a debatable issue of contemporary cognitive semantics, i.e. the issue of the psychological reality of explication procedures used in the framework of the conceptual metaphors theory proposed by G. Lakoff and M. Johnson. It quotes arguments that show the speculative and non-representative nature of such procedures in relation to many language metaphors. This is evidenced by a psycholinguistic experiment that was carried out for the purpose of the study. Its results indicate that the conceptual projections following Lakoff and Johnson are relatively rarely taken into account by respondents. An alternative conception of the cognitive interpretation of metaphor is proposed, based on the affordance phenomenon, i.e. the use of secondary nominations to fill in naming deficits, and also to facilitate mental processing of semantic information through concepts from the basic level of categorization.